2010
DOI: 10.1177/1091142110386214
|View full text |Cite
|
Sign up to set email alerts
|

Taxpayer Behavior When Audit Rules Are Known: Evidence from Italy

Abstract: Italy, which ranges among the OECD countries with the highest share of shadow economy, has adopted in 1998 a peculiar audit scheme (Studi di Settore), for small and medium enterprizes and self-employed. This scheme is based on a particular interaction between the Tax Agency and taxpayers, where the Tax Agency unveils part of the information used to develop its audit rule. We study this scheme by means of a simple theoretical model and test it using a sample of 23,000 firms in manufacturing sectors in 2005 tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Indeed, the fight against tax evasion is a common theme among Italian politicians and citizens (D'Attoma 2017). It is also referenced as the cause of many societal problems such as reductions in public spending and inequality (Santoro and Fiorio 2010;Alm et al 2017). Moreover, Italy is a country plagued by ineffective governance and perceived to be relatively corrupt.…”
Section: Country Selectionmentioning
confidence: 99%
“…Indeed, the fight against tax evasion is a common theme among Italian politicians and citizens (D'Attoma 2017). It is also referenced as the cause of many societal problems such as reductions in public spending and inequality (Santoro and Fiorio 2010;Alm et al 2017). Moreover, Italy is a country plagued by ineffective governance and perceived to be relatively corrupt.…”
Section: Country Selectionmentioning
confidence: 99%
“…During the first year of SDS application it clearly emerged that taxpayers reacted strategically on several dimensions. For instance, Santoro and Fiorio (2011) showed that reported revenues concentrated at the presumptive level within the very first years of SDS implementation. The RA reacted in various ways including with an extensive evidence-based TAL campaign, which started in 2005 and focused on some input reports.…”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed description and analysis of SDS, seeSantoro and Fiorio (2011) andSantoro (2008).…”
mentioning
confidence: 99%
“…Models have been developed to show that, when the Revenue Agency is budget-constrained, the optimal audit probability should be endogeneous, and, in particular, that it should depend on the amount of income reported [1]. Within BSS rules, models can be constructed to derive an income-conditional audit probability along with rational responses by the taxpayer (see [13] and [14]). However, these models are implicitly based on the assumption of full information.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Audit rules are based on Business sector studies, BSS, which were introduced in 1998 (see [13] and [14]). Businesses reporting a turnover (value of sales), R i , not higher than 5 millions of euros have to compare this reported value with a presumptive turnover defined as…”
Section: Institutional Backgroundmentioning
confidence: 99%